Understanding of human metabolic pathways of different sub-classes of phenols from Arbutus unedo fruit after an acute intake. Issue 3 (9th March 2016) - Mosele, Juana I.; Macià, Alba; Motilva, María-José
Abstract : Phenolic compounds of A. unedo are bioavailable in healthy adults. The main absorbed compounds are from gut microbial origin and can be detected through a simplified and less invasive method using dried blood spot (DBS) cards. Abstract : Arbutus unedo is a small Mediterranean fruit, commonly named strawberry tree, which is a rich source of different sub-classes of phenolic compounds, the more representative being the gallic acid derivatives, including its mono and oligomeric forms esterified with quinic and shikimic acids. In addition, galloyl derivatives, particularly gallotannins, described in A. unedo, are part of a very selective phenolic group, present in a reduced number of plant-products. The aim of the present study is to provide a better understanding of human metabolic pathways of different sub-classes of phenols from the A. unedo fruit after an acute intake by healthy adults. Therefore, the A. unedo phenolic metabolites were studied in whole blood samples (0 to 24 h), urine (24 h) and feces (12 and 24 h). Special focus was placed on the application of dried blood spot (DBS) cards for the sample collection and for the analysis of phenolic metabolites in whole blood samples. The results of the blood analysis revealed two peaks for the maximum concentrations of the main phenolic metabolites. Furthermore, it is appropriate to highlight the application of DBS cards as an efficient and accurate way to collect blood samples in post-prandial bioavailability studies. The analysis of urine (24 h) gave a wide range of phenolic metabolites showing the extensive metabolism that A. unedo phenolic compounds underwent in the human body. The results of the study provide a relevant contribution to the understanding of the in vivo human bioavailability of phenolic compounds, especially galloyl derivatives, a singular phenolic sub-group present in the A. unedo fruit.